QTL mapping of almond kernel quality traits in the F1 progeny of ‘Marcona’ × ‘Marinada’ - Pérez de los Cobos, Felipe; Romero, Agustí; Lipan, Leontina; Miarnau, Xavier; Arús, Pere; Eduardo, Iban; Batlle, Ignasi; Calle, Alejandro (Frontiers in Plant Science, 2024)
Almond breeding is increasingly focusing on kernel quality. However, unlike other agronomic traits, the genetic basis of physical and chemical kernel quality traits has been poorly investigated. To address this gap, we conducted a QTL mapping of these traits to enhance our understanding of their genetic control. We phenotyped fruit samples from an F1 population derived from the cross between 'Marcona' and 'Marinada' for up to four years, using conventional and image analysis methods. Additionally, the 91 individuals of the population were genotyped with the almond Axiom™ 60K SNP array, and highdensity linkage maps were constructed. These analyses identified several genomic regions of breeding interest. For example, two regions on chromosome one were found to contain QTLs for kernel shape and dimension, while another region at the end of the same chromosome contained QTLs for kernel fatty acid composition. Notably, QTLs for kernel symmetry and kernel shoulder, reported for the first time in this study, were also mapped on chromosome one. These QTLs will serve as a foundation for developing molecular markers linked to kernel physical and chemical quality traits in almonds, facilitating the integration of marker-assisted selection into breeding programs.